Empowering adolescents in Lucknow with rabies awareness: An interventional study - Vinita Shukla; Vandana Verma; Arvind Kumar Singh; Beena Sachan; Amit Kaushik; Rashmi Kumari; Sunil Dutt Kandpal; Sugandha Jauhari; Chhaya Singh; Shruti Singh (Journal of Family Medicine and Primary Care)
Background: Rabies is a preventable viral zoonotic disease that remains a significant public health issue, especially in developing countries like India. Despite the availability of vaccines and post-exposure prophylaxis, rabies incidence, particularly from dog bites, is high. Aims and Objectives: This study aimed to assess the need for health education about rabies among adolescents in Lucknow, Uttar Pradesh, India, and evaluate the effect of health awareness interventions on their knowledge. Material and Methods: A single-arm interventional study was conducted at rural and urban health centers in Lucknow, involving 401 adolescents, aged 10–19 years. Participants were selected using stratified multistage random sampling. Data were collected through interviews using a pretested questionnaire. The intervention included health awareness camps featuring lectures, demonstrations, and wall paintings. Pre- and post-intervention data were analyzed using SPSS 29.0, with the McNemar test and paired t-tests used to evaluate changes in knowledge. Results: Of the 401 adolescents, 199 in rural and 202 in urban areas completed the posttest. Awareness of rabies being 100% fatal increased from 9% to over 40% in rural areas, and from 12% to over 50% in urban areas. Significant improvements were also observed in knowledge about proper wound management and the need for vaccination after animal bites. The overall mean score of correct responses increased significantly in both rural and urban areas. Conclusion: The study highlighted a critical need for better rabies awareness among adolescents in Lucknow. Educational interventions significantly improved knowledge, emphasizing the importance of targeted health education in preventing rabies.